Study of Risk Level Death Based on Clinical Symptoms in Cases of Canine Leptosprirosis in Jakarta, Depok and South Tangerang: Data from January-August 2020 - Ambar Retnowati; Agustin Indrawati; Upik Kesumawati; Safika Safika; Pratitis S Wibowo; Susan M Noor; Uus Saepuloh (Jurnal Sain Veteriner, 2023)
Leptospirosis is a zoonotic disease caused by bacteria Leptospira sp. which causes infection in animals and humans. Dogs infected with leptospirosis showed symptoms such as anorexia, fever, vomiting, weakness, diarrhea and often experience yellowing of the eye area and mucosa around the mouth (icteric) with fatal systemic complications and multi-organ dysfunction, especially in the kidneys and liver. Leptospirosis is an endemic disease in Jakarta. This study aims to identify risk factors that can contribute to canine mortality based on early clinical symptoms that are found when the dog is in an animal health service facility such as a veterinary clinic, veterinary hospital, or independent practice veterinarian. Method was used in this study is clinical manifestations and laboratory examinations and medical records of dogs with suspected leptospirosis. Criteria inclusions were based on aspects of the clinical symptoms of dogs in and around Jakarta. Analysis data used the chi-square with confidence of interval (CI) 95%. Dogs used during the study had ages for puppies (less than 1 year) totaling 13 or 32.50%, for adult dogs over 1 year amounted to 27 or 67.50%, 80% male dogs and 20% female. with 80% maintenance system not housed by the owner. And the conclusion is risk factors for clinical symptoms such as myalgia, symptomatic vomiting of the pulmonary area or shortness of breath and abdominal pain, conjunctival suffusion, anorexia and diarrhea contributed to the high mortality rate leptospirosis during study in dogs 2020.